A general strategy for embedding ultrasmall CoMx nanocrystals (M = S, O, Se, and Te) in hierarchical porous carbon nanofibers for high-performance potassium storage. Issue 3 (15th January 2021) - Lai, Chenling; Zhang, Zhuangzhuang; Xu, Yifan; Liao, Jiaying; Xu, Zhenhua; Yi, Zuyue; Xu, Jingyi; Bao, Jianchun; Zhou, Xiaosi
Abstract : Hierarchical porous carbon nanofibers with intimately coupled Co-based ultrasmall nanoparticles and a carbon substrate are prepared by a universal strategy, exhibiting improved potassium storage properties. Abstract : Closely integrated transition-metal-based compounds/carbon nanoarchitectures are one of the most promising anode materials for large-scale energy storage applications because of the superior structural stability and the outstanding synergistic effect from the efficient combination of the two components. Herein, a versatile strategy is demonstrated for fabricating hierarchical porous carbon nanofibers (HCFs) with closely coupled Co-based ultrafine nanoparticles and a carbon matrix. The spatially restricted reactions of the synthetic method can not only prevent the agglomeration of the nanoparticles, but also provide extremely tight coupling interaction between CoM x (M = S, O, Se, and Te) nanoparticles and conductive carbon nanofibers. As a proof of concept, the as-fabricated CoS2 @HCFs show high reversible capacity, excellent rate property, and ultralong cycling life when evaluated as an anode material for potassium-ion batteries (PIBs). Even after 1000 cycles, the charge capacity can be retained at 268 mA h g −1 at an elevated current rate of 500 mA g −1, one of the highest reported performances for Co-based anode materials in PIBs. This work emphasizes the importance of designing and manufacturing highly functionally coupled hybrid materials for improved energy storage implementation.